A Catalogue of 18th-Century Symphonies - LaRue, Jan (Indiana University Press, 1988)
A Catalogue of 18th-Century Symphonies makes possible for the first time a comprehensive view of one of the largest and most significant repertories in the history of music. Until now, no one has known for certain who wrote what, and hundreds of symphonies have been attributed in manuscript and printed sources to two or more composers. Under these conditions no reliable history of the symphony could be written. Now, thanks to Jan LaRue·s indefatigable efforts, we know how many symphonies have survived from the eighteenth century, where they are, their composers, and how many each composer wrote; and we can see at a glance the favorite keys, movement sequences, and instrumental combinations that were used. Volume I, Thematic Identifier, enables the user to identify more than 13,000 symphonies by means of the note names of the opening bars of the first violin part. This powerful reference tool also tells whether a particular symphony exists anywhere under a different name and whether there are any anonymous sources for the work. Volume II, Composers' Worklists, will provide detailed information for all the symphonies attributed to a particular composer in Volume I. With this indispensable bibliographic resource, Jan LaRue has established a solid foundation for public reference, performance, recording, and future research.